Effect of HIF-1Î±siRNA-linked AuNRs on radiotherapy of nasopharyngeal carcinoma - Xu, Gang; Zhang, Haosheng; Li, Zhibin; Wu, Shihai; Quan, Rencui; Mao, Kun; Sheng, Yang; Li, Xianming (Cellular and Molecular Biology, 2020)
The radiation sensitivity of tumor cells is closely related to tumor cell hypoxia. Hypoxia-inducible factor-1Î± (HIF-1Î±) is considered a key transcription factor which regulates the sensitivity of hypoxic tumor cells to radiotherapy. On the other hand, some studies have shown that gold nanomaterials improve radiation sensitivity. However, studies on the effect of gold nanomaterials carrying HIF-1Î±siRNA on tumor radiotherapy, and the underlying mechanisms are limited. Thus, the present study was aimed at investigating the effect of gold nanocomposites (AuNRs) carrying HIF-1Î±siRNA (AuNRs-HIF-1Î±siRNA) on the radiation sensitivity of nasopharyngeal carcinoma (NPC) hypoxia cells. The effect of AuNRs-HIF-1Î±siRNA on radiation sensitivity of hypoxic NPC cells was determined under X-ray irradiation. The results showed that Au-HIF-1Î±siRNA improved the radio-sensitivity of NPC tumor. Thus, this study has demonstrated that gold nanomaterials carrying HIF-1Î±siRNA effectively increased the radio-sensitivity of hypoxic tumor, thereby improving the effect of radiotherapy on NPC cells.